Biodiversity conservation: local and global consequences of the application of "rights of nature" by Ecuador. Issue 1 (1st January 2021) - Guayasamin, Juan M.; Vandegrift, Roo; Policha, Tobias; Encalada, Andrea C.; Greene, Natalia; Ríos-Touma, Blanca; Endara, Lorena; Cárdenas, Rafael E.; Larreátegui, Fred; Baquero, Luis; Arcos, Inty; Cueva, José; et al.
ABSTRACT: In 2008, Ecuador recognized the Constitutional Rights of Nature in a global first. This recognition implies a major shift in the human-nature relationship, from one between a subject with agency (humans) and an exploitable object (nature), to a more equilibrated relationship. However, the lack of a standard legal framework has left room for subjective interpretations and variable implementation. The recent widespread concessioning of pristine ecosystems to mining industries has set up an unprecedented conflict and test of these rights. Currently, a landmark case involving Los Cedros Protected Forest and mining companies has reached the Constitutional Court of Ecuador. If Ecuador's highest Court rules in favor of Los Cedros and the Rights of Nature, it would set a legal precedent with enormous impact on biological conservation. Such a policy shift offers a novel conservation strategy, through citizen oversight and action. A ruling against Los Cedros and the Rights of Nature, while a major setback for biodiversity conservation, would be taken in stride by the active social movement supporting these goals, with the case likely moving into international courts. Meanwhile, extractive activities would continue and expand, with known consequences for biodiversity.